The actions of thyroxine on the uterus during peri-implantation and implantation periods in rats / Abu Sadat Md. Sayem - Abu Sadat, Md. Sayem (2018)
Thyroid hormone plays important role in modulating the uterine reproductive events. However, the mechanisms underlying the action of this hormone in the uterus particularly during embryo implantation have not been fully identified. In order to understand these, in this study, effects of thyroxine on the uterus during periimplantation and implantation periods were investigated. These include identifying changes in the uterine expression of the receptors related to thyroid hormone functions i.e. thyroid hormone receptor (TR-α and β), thyroid stimulating hormone receptor (TSHR), retinoic acid receptor (RAR), retinoic X receptor (RXR), vitamin D receptor (VDR) and extracellular signal-regulated kinase (ERK1/2). Further, changes in expression of these proteins under the influence of sex-steroids were also identified. In addition, effects of thyroxine on expression of aquaporins (AQP) protein which is important in uterine fluid homeostasis and the expression of the proteins related to uterine receptivity development such as integrin αvβ3, E-cadherin, Msx-1 and Ihh in the uterus during peri-implantation periods were analyzed. Studies were conducted using two models: (i) methimazole-induced hypothyroid pregnant rats treated with different doses of thyroxine (20, 40 and 80 µg/kg/day) and (ii) rats under different sex-steroid influence (both ovariectomised, sex-steroid replaced and intact at different phases of the oestrous cycle). Finally, the effects of thyroxine treatment on embryo implantation rate were determined. Results: In model (i), expression of TRα-1, TRβ-1, RXR and ERK1/2 proteins in the uterus during peri-implantation period increased with increasing doses of thyroxine. These proteins were found to be distributed in the stroma at a relatively higher amount following thyroxine treatment. Meanwhile, thyroxine treatment causes increased in expression of TRα-1, TRβ-1, TSHR, RAR and ERK1/2 proteins and mRNAs in the uterus during implantation period. Peri-implantation uterus had its luminal size decrease following treatment with thyroxine with an associated decrease in iv expression of AQP-1, 5 and 7. Thyroxine treatment increases expression of the uterine receptivity proteins i.e. integrin αvβ3, E-cadherin, Msx-1 and Ihh during periimplantation period. The numbers of embryo implantation were also found to increase by thyroxine. In the meantime, treatment of ovariectomised rats with estradiol (E2) increases the expression of TRα-1, TRβ-1, TSHR, VDR, RAR and ERK1/2 with expression of these proteins were increased at estrus phase of the oestrous cycle, under E2 dominance. These proteins were found to be distributed in the uterine luminal and glandular epithelia and stroma. Following progesterone (P) treatment and at diestrus phases of the oestrous cycle (under P dominance), expression of these proteins was lesser as compared to under E2 influence and were found to be distributed only in the uterine stroma. Conclusions: The changes as documented above could explain the important role of thyroxine on the uterus during peri-implantation and implantation periods as well as help to explain the role of sex-steroids in regulating thyroxine function in the uterus. Dysregulations in these parameters could potentially lead to infertility